Unihemispheric burst suppression - Edward C. Mader Jr; Nicole R. Villemarette-Pittman; Cornel T. Rogers; Frank Torres-Delgado; Piotr W. Olejniczak; John D. England (MDPI AG, 2014)
Burst suppression (BS) consists of bursts of high-voltage slow and sharp wave activity alternating with periods of background suppression in the electroencephalogram (EEG). When induced by deep anesthesia or encephalopathy, BS is bihemispheric and is often viewed as a non-epileptic phenomenon. In contrast, unihemispheric BS is rare and its clinical significance is poorly understood. We describe here two cases of unihemispheric BS. The first patient is a 56-year-old woman with a left temporoparietal tumor who presented in convulsive status epilepticus. EEG showed left hemispheric BS after clinical seizure termination with lorazepam and propofol. The second patient is a 39-year-old woman with multiple medical problems and a vague history of seizures. After abdominal surgery, she experienced a convulsive seizure prompting treatment with propofol. Her EEG also showed left hemispheric BS. In both cases, increasing the propofol infusion rate resulted in disappearance of unihemispheric BS and clinical improvement. The prevailing view that typical bihemispheric BS is non-epileptic should not be extrapolated automatically to unihemispheric BS. The fact that unihemispheric BS was associated with clinical seizure and resolved with propofol suggests that, in both cases, an epileptic mechanism was responsible for unihemispheric BS.